A Blot on the Landscape: Consensus and Controversies on Wind Farms in Rural Portugal - Delicado, Ana (2017)
In recent years, Portugal has witnessed the siting of 250 wind farms, particularly in mountainous and rural areas. Even though, unlike other European countries, general public consensus seemed at first to prevail, protests by local population and ENGOs have been increasing of late (many broadcast by the media) the outcomes of Environmental Impact Assessments (EIAs) provide a good example. This chapter has two main objectives. On one hand, it examines how rural landscapes are discursively framed in the press when the Portuguese media picks up wind energy issues. On the other hand, by analysing EIA reports, it aims at identifying the social actors involved in the decision process of the siting of wind farms in rural or periurban areas, the arguments for and against the location of these facilities and how the (rural) landscape is framed and represented. The empirical material is drawn on three different sources: media analysis of the public discourse on landscape issues related to wind farms; an analysis of EIA reports regarding wind farms in Portugal and an analysis of official positions on this issue assessed through the Environmental Impact Declarations (EID) of EIA processes. It is concluded that despite the lack of media attention to landscape impacts’ of wind farms, the existing discursive frames are often attached to dichotomized cultural meanings: it either deems wind farms as technological tools for landscape progressive transformation or as a risk to its pristine image. As to the EIA reports, landscape matters are more visible and important and at times sufficient to reject approval or change of the siting of a wind farm.